ANALISIS PUTUSAN PENGADILAN TERHADAP PERKARA WANPRESTASI PERJANJIAN JUAL BELI KIOS (Nomor 18/PDT.G/2016/PN.KPG) - Ravikah Amelia; Osihanna Meita Kasih; Sefrina Linda Adilla Putri; Angelica Nathaniella; Sulastri, Sulastri (Causa: Jurnal Hukum dan Kewarganegaraan, 2024)
This study aims to analyze the decision of the Kuningan District Court in the case of breach of contract regarding a sale and purchase agreement for a kiosk, case number 18/PDT.G/2016/PN.KPG. The primary focus of this research is to identify how Indonesian civil law addresses and provides solutions to breach of contract disputes in the context of a sale and purchase agreement, as well as to evaluate the accuracy of the application of relevant legal principles in the court's ruling. Using a normative legal approach, the study examines the legal reasoning employed by the judge in assessing the non-fulfillment of contractual obligations and the legal consequences of breach of contract for the parties involved. The findings show that the court's decision upholds justice by carefully considering the evidence presented by the parties and referring to the applicable legal provisions, particularly regarding compensation and the fulfillment of contractual duties. This study is expected to contribute to a better understanding of contract law application in Indonesia and offer recommendations for resolving similar disputes in the future.